2007
DOI: 10.3174/ajnr.a0737
|View full text |Cite
|
Sign up to set email alerts
|

The Hypodense Focus in the Petrous Apex: A Potential Pitfall on Multidetector CT Imaging of the Temporal Bone

Abstract: BACKGROUND AND PURPOSE:Hypoattenuated foci in the otic capsule are routinely identified on multidetector CT (MDCT), particularly in pediatric patients. We aimed to describe and characterize the hypoattenuated focus in the anterior otic capsule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 7 publications
(9 reference statements)
1
15
0
1
Order By: Relevance
“…Therefore, the image processing algorithm is required to be as simple as possible. However, although an evaluation of subtle temporal bone anatomical structures is generally performed by high-resolution CT [3,8,9], image quality of the petrous part of the temporal bone was markedly reduced in the improved multi-kernel images (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the image processing algorithm is required to be as simple as possible. However, although an evaluation of subtle temporal bone anatomical structures is generally performed by high-resolution CT [3,8,9], image quality of the petrous part of the temporal bone was markedly reduced in the improved multi-kernel images (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…This should not be mistaken for normal pericochlear hy poattenuating foci, or "cochlear clefts" (Fig 26), seen in children with no ev idence of otosclerosis and no history of osteogenesis imperfecta (63,64). There are various theories as to what the cochlear cleft represents (63)(64)(65), but it is widely believed to be related to normal variant development of the otic capsule, since the finding is highly …”
Section: Figure 24mentioning
confidence: 92%
“…The endosteal layer of bone surrounding the otic capsule ossifies at midgestation and does not change after birth; the middle layer, however, is partly calcified in the near-term fetus but then is rapidly replaced by bone. 4 EO is completed finally in the region of the FAF, which is a cleft between the inner and middle layers just anterior to the oval window. 5 Fibrocartilage may persist at the FAF even in adults; this region is also a site of predilection for otosclerosis (probably due to the presence of specific cartilage constituents targeted by autoimmune reactions).…”
Section: Discussionmentioning
confidence: 99%
“…In a CT study evaluating ossification features of the OC, 4 it has been shown that incomplete ossification of the entire middle otic layer in a neonate skull specimen was seen as a hypoattenuated halo surrounding the cochlea ( . This appearance is similar to that in our cases labeled extensive iEO; thus, extensive iEO probably reflects the earliest appearance of a completely nonossified middle layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation